ARALOSIDE A METHYL ESTER FROM PANAX BIPINNATIFIDUS SEEM PROTECTS H9C2 CARDIOMYOCYTES AGAINST CHEMICAL HYPOXIA/REOXYGENATION- INDUCED INJURY BY PRESERVING MITOCHONDRIAL FUNCTION - Ngo, Thi Hai Yen; Pham, Thi Bich; Tran, Duc Khanh; Ly, Tu Van; Phung, Quang Huy; Vu, Thi Thu (Tạp chí Sinh lý học Việt Nam, 2023)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-18" data-turn-id-container="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-18" data-testid="conversation-turn-38" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="6ac53975-e838-4819-a6f1-69590d1aa8ce" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> Panax bipinnatifidus Seem (PB) is a precious herb used in many traditional remedies in Vietnam. Previous studies have proven that the saponin-rich extract of this herb has a protective effect on cardiomyocytes in hypoxia-reoxygenation injury (HR). However, which compound in PB plays a major role in this effect has not been elucidated. Therefore, this study was conducted to evaluate the effects of saponin extracted from PB extract, Araloside A Methyl Ester (AAME) on H9C2 cardiomyocytes in HR injury. Cells were grown in normal conditions (control) and HR-CoCl2 conditions, and AAME was added to the culture medium during reoxygenation. Cell viability and some mitochondrial indices (cardiolipin content, mitochondrial membrane potential, ROS) were determined by suitable kits. The results showed that AAME at concentrations of 10 μM significantly reduced the cell death rate by limiting mitochondrial dysfunction (preserving cardiolipin content and mitochondrial membrane potential, reducing mitochondrial ROS) of H9C2 cells in HR-CoCl2 injury (p<0,05). This result demonstrated the potential of AAME to protect cardiomyocytes from HR injury.